2023
DOI: 10.1021/acs.accounts.3c00221
|View full text |Cite
|
Sign up to set email alerts
|

Selection Criteria for Small-Molecule Inhibitors in Area-Selective Atomic Layer Deposition: Fundamental Surface Chemistry Considerations

Abstract: Metrics & MoreArticle Recommendations CONSPECTUS: Atomically precise and highly selective surface reactions are required for advancing microelectronics fabrication. Advanced atomic processing approaches make use of small molecule inhibitors (SMI) to enable selectivity between growth and nongrowth surfaces. The selectivity between growth and nongrowth substrates is eventually lost for any known combinations, because of defects, new defect formation, and simply because of a Boltzmann distribution of molecular re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Details are available in the Methods section. The etching step was followed by 5 “cycles” of DMATMS as a small molecule inhibitor (SMI; Figure c). ,, Finally, the substrates were exposed to alternating doses of titanium tetrachloride, TiCl 4 , and water, for t-TiO 2 AS-ALD (Figure d,e) and TiCl 4 and N 2 /H 2 plasma for p-TiON AS-ALD (Figure f,g). A total of 100 and 250 ALD cycles were applied for t-TiO 2 and 250 to 450 cycles for p-TiON.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Details are available in the Methods section. The etching step was followed by 5 “cycles” of DMATMS as a small molecule inhibitor (SMI; Figure c). ,, Finally, the substrates were exposed to alternating doses of titanium tetrachloride, TiCl 4 , and water, for t-TiO 2 AS-ALD (Figure d,e) and TiCl 4 and N 2 /H 2 plasma for p-TiON AS-ALD (Figure f,g). A total of 100 and 250 ALD cycles were applied for t-TiO 2 and 250 to 450 cycles for p-TiON.…”
Section: Resultsmentioning
confidence: 99%
“…An overview of such modification strategies can be found elsewhere. 12 Several area-selective ALD (AS-ALD) processes have been developed so far, 9−11,13−15 yet the selective deposition of hardmask materials on SiN as GS with respect to SiO 2 as NGS has been an extremely challenging target to achieve. AS-ALD of TiN, TiO 2 , and other typical hard-mask materials on SiN vs SiO 2 materials that are ubiquitous in almost every device patterning step, could dramatically expand the processing window of several patterning processes employed in semiconductor manufacturing.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In another approach, the modification of a surface with an organic material can be used to deactivate it and inhibit film growth. The latter strategy may offer the versatility of selectively coating a broad number of metal or dielectric surfaces commonly encountered in device builds. Organic inhibiting materials can be deposited either by solution or vapor-phase methods, generally dependent on the vapor pressure of the molecule. , Solution deposition methods often use self-assembled monolayers (SAMs) to form densely packed inhibiting layers, driven in large part by headgroup chemistry, which presents a strong enthalpic driving force to bind with a surface (such as thiols, phosphonic, and hydroxamic acids). Formation of the monolayer is further aided by interactions between aliphatic side chains through van der Waals forces to form crystalline monolayers (the magnitude of the interaction depends on the length of the side-chain) .…”
Section: Introductionmentioning
confidence: 99%
“…Few papers have reported ASD processes for GST and Sb 2 Te 3 ASD by ALD and CVD . Pore et al reported the ALD of GST at the low temperature of 70 °C by utilizing dechlorosilylation chemistry, and several research groups have demonstrated ALD of GST based on this chemistry. , Low-temperature ALD in principle creates opportunities to utilize a wide range of small molecule inhibitors (SMIs), polymers, or self-assembled monolayers (SAMs) to enable ASD, as thermal degradation of the passivation can be minimized. , However, no in-depth investigation of ASD by means of the dechlorosilylation chemistry has been reported, to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%